Tax increment financing as a municipal revenue: helping the legislature get it right - Novak, Terry L. (1999)
Tax increment financing raises revenue for public infrastructure in a redevelopment district by capturing increased property tax revenue stimulated by the redevelopment. TIF has left a long trail of intergovernmental controversy. Cities in Washington State, which approved TIF in 1982, have yet to complete a project. After two failed constitutional amendment campaigns, a test case was initiated to validate TIF before the state supreme court. The cities lost. This article examines the technique, this case, and lessons for making tax increment financing available as a revenue source in Washington. - Reproduced
Keywords: Revenue; Public finance; Local finance